Design method and preparation method of germanium substrate 2-13 [mu] m middle and far infrared anti-reflection film

By designing the alternating film layer structure of Ge, ZnS, YF3, and Y2O3 films on the germanium substrate, optimizing the film thickness and strengthening the outermost layer, the problem of insufficient light transmittance in the far-infrared band of the germanium substrate is solved, and high transmittance is achieved and corrosion resistance, suitable for high-precision optical systems.

CN119247526AActive Publication Date: 2025-01-03安徽光智科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411279967.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-03
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The lack of light transmittance of germanium substrates in the far infrared band limits its application in high-precision optical systems, especially in the 2-13μm band.

Method used

Design a germanium base 2-13μm medium- and far infrared induced impermeable film. By using four film materials, Ge, ZnS, YF3 and Y2O3, an alternating film layer structure is formed, the film thickness is optimized to improve transmittance, and used in the outermost layer. YF3 is reinforced with Y2O3 to form a protective layer to improve hardness and moisture-proof corrosion resistance.

Benefits of technology

The transmittance of the 2-13μm medium and far infrared band of the germanium substrate is achieved to meet the requirements, and the moisture-proof and corrosion resistance of the film system is improved, ensuring reliable application in high-precision optical systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119247526A_ABST
    Figure CN119247526A_ABST
Patent Text Reader

Abstract

The invention provides a design method and a preparation method of a germanium substrate 2-13 [mu] m middle and far infrared antireflection film. The design method of the germanium substrate 2-13 [mu] m middle and far infrared antireflection film comprises the following steps: selecting 6.5 [mu] m as a reference wavelength for designing a 1 / 4 wavelength film thickness of an optical film, and using a film stack formula: Sub / 0.04 L / 0.3 H / 0.1 L / 0.3 H / 0.2 L / 0.2 H / 0.3 L / 0.1 H / 0.5 L / 0.03 M / 0.2 L / 0.2 M / 0.15 L / 0.6 M / 0.02 Q / AIR, wherein Sub is a germanium substrate, AIR represents air, H represents Ge of the 1 / 4 wavelength film thickness, L represents ZnS of the 1 / 4 wavelength film thickness, M represents YF3 of the 1 / 4 wavelength film thickness, and Q represents Y2O3 of the 1 / 4 wavelength film thickness; the film thickness is optimized through software, the optimal film thickness is obtained, and the transmittance of the optimized germanium substrate at the wave band of 2-13 microns meets the requirement; and inputting the optimized film thickness into a control computer of the coating machine. The preparation method of the 2-13 [mu] m middle and far infrared anti-reflection film on the germanium substrate comprises the following steps: S1, cleaning before plating and preparing a film material; s2, configuring technological parameters of the film system; s3, vacuumizing, baking and premelting the film material at constant temperature; s4, ion source cleaning; s5, plating and monitoring a film layer; s6, keeping at a constant temperature after plating; s7, cooling and workpiece taking; and S8, the step S1 to the step S7 are repeated, and the second face is plated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of infrared coating technology, and more specifically to a design method and a preparation method of a 2-13 μm mid- and far-infrared anti-reflection film on a germanium substrate. Background Art

[0002] Mid- and far-infrared filters are needed in infrared temperature measuring instruments and thermal imagers. Infrared temperature measuring instruments and thermal imagers generally work in the range of 2-13μm, and germanium has good transmittance in the mid- and far-infrared, and is not transparent in the visible light band. Since germanium itself is very high, with a refractive index slightly greater than 4 (dimensionless), and a reflectivity of up to 36%, the material itself also has a certain absorption of light, resulting in insufficient transmittance in specific bands. The transmittance is less than 47%, which greatly limits its application in some high-precision optical systems, especially in the ultra-wide mid- and far-infrared band of 2-13μm.

[0003] How to deposit a reliable optical film on a germanium substrate to improve the transmittance in the 2-13μm band and how to design the film system and prepare the film layer have become technical problems that need to be solved urgently in the field of optical films. Summary of the invention

[0004] In view of the problems existing in the background technology, an object of the present invention is to provide a design method and a preparation method of a 2-13μm mid- and far-infrared anti-reflection film on a germanium substrate, which can ensure that the transmittance of the designed and prepared germanium substrate in the 2-13μm mid- and far-infrared band meets the requirements.

[0005] Another object of the present disclosure is to provide a design method and a preparation method for a 2-13 μm mid- and far-infrared anti-reflection film on a germanium substrate, which enables the film structure to improve moisture resistance and corrosion resistance.

[0006] Thus, a method for designing a germanium substrate 2-13 μm mid-to-far infrared anti-reflection film comprises the following steps: Sa, selecting 6.5 μm as a reference wavelength for designing an optical film with a film thickness of 1 / 4 wavelength, and using a film stack formula: Sub / 0.04L / 0.3H / 0.1L / 0.3H / 0.2L / 0.2H / 0.3L / 0.1H / 0.5L / 0.03M / 0.2L / 0.2M / 0.15L / 0.6M / 0.02Q / AIR, wherein Sub is a germanium substrate, AIR represents air, H represents a high refractive index material Ge (germanium) with a film thickness of 1 / 4 wavelength, L represents a low refractive index material ZnS (zinc sulfide) with a film thickness of 1 / 4 wavelength, and M represents an intermediate refractive index material YF with a film thickness of 1 / 4 wavelength. 3 (yttrium fluoride), Q represents the outermost layer material Y of the film layer with a thickness of 1 / 4 wavelength 2 O 3(yttrium oxide); Sb, the film thickness is calculated and optimized through the design software to obtain the best film thickness. The transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13μm meets the requirements; Sc, the optimized film thickness is input into the control computer of the coating machine.

[0007] A method for preparing a 2-13 μm mid-to-far infrared antireflection film on a germanium substrate comprises the following steps: S1, before plating, cleaning the accompanying plated sheet and the product of the germanium substrate as a lens and performing the steps of Ge, ZnS, YF 3 , Y 2 O 3 Four types of film material preparation work; S2, film system process parameter configuration, the film system process parameter configuration includes the optimal film thickness, film material evaporation mode, film material deposition rate, and the use of ion source assisted deposition. The film thickness in the film system process parameters is based on the aforementioned optimal film thickness stored in the control computer of the coating machine; S3, the cleaned lenses are placed in the fixture, the fixture with the lenses placed is hung in the cavity of the coating machine, and the vacuum baking and film material pre-melting, degassing, impurity removal and constant temperature are carried out; S4, ion source cleaning of the lenses; S5, film coating and monitoring, the film layer is coated on the first side of the lens according to the film system parameter process configuration of step S2; S6, constant temperature maintenance after coating; S7, cooling and taking out the parts; S8, repeating steps S1 to S7, and coating the second side of the lens.

[0008] The beneficial effects of the present disclosure are as follows.

[0009] In the design method and preparation method of the germanium substrate 2-13 μm mid-to-far infrared anti-reflection film according to the present disclosure, Ge, ZnS, YF 3 , Y 2 O 3 Four kinds of film materials, Ge, ZnS as high and low refractive index materials, YF 3 As the intermediate refractive index material, ZnS is selected as the bottom layer material in combination with the germanium substrate, and YF is used as the outermost layer 3 With Y 2 O 3 The outermost protective layer is formed by the reinforcement combination, ZnS and Ge form the first to eighth layers alternately, and ZnS and YF 3 By forming the alternating ninth to fourteenth layers, the transmittance of the designed germanium substrate in the mid-to-far infrared band of 2-13 μm can meet the requirements.

[0010] In the design method and preparation method of the 2-13 μm mid-to-far infrared antireflection film on a germanium substrate according to the present disclosure, by using YF 3 With Y 2 O 3 The outermost protective layer is formed by reinforcing and combining Ge, ZnS, and YF3 , Y 2 O 3 When the transmittance of the four membrane materials and the germanium substrate meets the requirements in the mid-to-far infrared band of 2-13μm, the outermost protective layer in the designed membrane structure plays a role in improving hardness, enhancing resistance to mechanical friction and moisture and corrosion resistance, especially improving moisture and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a schematic structural diagram of a film stack design optimization diagram according to the design method of a 2-13 μm mid- and far-infrared anti-reflection film on a germanium substrate disclosed in the present invention.

[0012] Figure 2 It is a transmittance curve diagram of the film stack design optimization diagram of the design method of the germanium substrate 2-13 μm mid- and far-infrared anti-reflection film according to Example 1 of the present disclosure.

[0013] Figure 3 It is a curve diagram of the transmittance in the 2-13 μm band of the accompanying coating sheet of Example 1 coated with 2-13 μm mid- and far-infrared anti-reflection films on both sides. DETAILED DESCRIPTION

[0014] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0015] [Design method of 2-13μm mid- and far-infrared antireflection film on germanium substrate]

[0016] The design method of the 2-13 μm mid- and far-infrared antireflection film on a germanium substrate disclosed in the present invention comprises the following steps:

[0017] Sa, 6.5μm is selected as the reference wavelength for the design of 1 / 4 wavelength film thickness of optical thin films, using the film stack formula:

[0018] Sub / 0.04L / 0.3H / 0.1L / 0.3H / 0.2L / 0.2H / 0.3L / 0.1H / 0.5L / 0.03M / 0.2L / 0.2M /

[0019] 0.15L / 0.6M / 0.02Q / AIR,

[0020] Among them, Sub is the germanium substrate, AIR represents air, H represents the high refractive index material Ge (germanium) with a film thickness of 1 / 4 wavelength, L represents the low refractive index material ZnS (zinc sulfide) with a film thickness of 1 / 4 wavelength, and M represents the intermediate refractive index material YF with a film thickness of 1 / 4 wavelength. 3(yttrium fluoride), Q represents the outermost layer material Y of the film layer with a thickness of 1 / 4 wavelength 2 O 3 (yttrium oxide);

[0021] Sb, the film thickness is calculated and optimized by design software to obtain the best film thickness. The transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13μm meets the requirements;

[0022] Sc, the optimized film thickness is input into the control computer of the coating machine.

[0023] In the design method of the 2-13 μm mid-to-far infrared antireflection film on a germanium substrate according to the present disclosure, Ge, ZnS, YF 3 , Y 2 O 3 Four kinds of film materials, Ge, ZnS as high and low refractive index materials, YF 3 As the intermediate refractive index material, ZnS is selected as the bottom layer material in combination with the germanium substrate, and YF is used as the outermost layer 3 With Y 2 O 3 The outermost protective layer is formed by the reinforcement combination, ZnS and Ge form the first to eighth layers alternately, and ZnS and YF 3 By forming the alternating ninth to fourteenth layers, the transmittance of the designed germanium substrate in the mid-to-far infrared band of 2-13 μm can meet the requirements.

[0024] In the design method of the 2-13 μm mid-to-far infrared antireflection film on a germanium substrate according to the present disclosure, by using YF 3 With Y 2 O 3 The outermost protective layer is formed by reinforcing and combining Ge, ZnS, and YF 3 , Y 2 O 3 When the transmittance of the four film materials and the germanium substrate meets the requirements in the mid-to-far infrared band of 2-13μm, the outermost protective layer in the designed film structure plays a role in improving hardness, enhancing resistance to mechanical friction and moisture and corrosion resistance, especially improving moisture and corrosion resistance.

[0025] In one example, in step Sb, for each of the two sides of the germanium substrate, the optimal film thickness is: the film thickness of the first ZnS film layer is 26.25±3nm, the film thickness of the second Ge film layer is 103.16±3nm, the film thickness of the third ZnS film layer is 71.92±3nm, the film thickness of the fourth Ge film layer is 102.24±3nm, the film thickness of the fifth ZnS film layer is 120.86±3nm, the film thickness of the sixth Ge film layer is 70.99±3nm, the film thickness of the seventh ZnS film layer is 185.15±3nm, the film thickness of the eighth Ge film layer is 33.83±3nm, the film thickness of the ninth ZnS film layer is 337.30±3nm, and the film thickness of the tenth YF film layer is 100. 3 The film thickness of the film layer is 29.96±3nm, the film thickness of the eleventh ZnS film layer is 157.82±3nm, and the film thickness of the twelfth YF 3 The thickness of the film layer is 204.99±3nm, the thickness of the thirteenth ZnS film layer is 95.64±3nm, and the thickness of the fourteenth YF 3 The thickness of the film layer is 602.18±3nm, and the fifteenth layer Y 2 O 3 The film thickness is 20±5nm. Figure 1 For each of the two sides of the germanium substrate, the overall thickness of the film structure formed by the fifteen film layers is 2162.29±47nm.

[0026] Accordingly, in one example, in step Sb, the transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13 μm is greater than 95% on average. Figure 2 shown.

[0027] In step Sb, the design software may be, but is not limited to, TFCalc, Essential Macleod, OptiLayer, Filmstar, Filmmaster, Autofilm, etc.

[0028] [Preparation method of 2-13μm mid- and far-infrared antireflection film on germanium substrate]

[0029] The method for preparing a 2-13 μm mid-to-far infrared antireflection film on a germanium substrate disclosed herein comprises the following steps:

[0030] S1, before plating, clean the accompanying plated sheets and products used as the germanium substrate of the lens and the Ge, ZnS, YF 3 , Y 2 O 3 Four types of film material preparation;

[0031] S2, film system process parameter configuration, the film system process parameter configuration includes the optimal film thickness of the film layer, the evaporation mode of the film material, the deposition rate of the film material, and the use of ion source assisted deposition. The film thickness in the film system process parameters is based on the aforementioned optimal film thickness stored in the control computer of the coating machine;

[0032] S3, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake, pre-melt the film material, release air, remove impurities and keep the temperature constant;

[0033] S4, ion source cleaning lens;

[0034] S5, coating and monitoring the film layer, coating the film layer on the first surface of the lens according to the film system parameter process configuration of step S2;

[0035] S6, constant temperature maintenance after plating;

[0036] S7, cooling and picking up;

[0037] S8, repeating steps S1 to S7 to perform film coating on the second surface of the lens.

[0038] In the method for preparing a 2-13μm mid-to-far-infrared anti-reflection film on a germanium substrate according to the present invention, steps S1 to S8 are performed and the thickness of the film layer in the film system process parameters of step S2 is based on the optimal film thickness stored in the control computer of the coating machine according to the aforementioned design method for a 2-13μm mid-to-far-infrared anti-reflection film on a germanium substrate according to the present invention, so that the transmittance of the prepared germanium substrate in the 2-13μm mid-to-far-infrared band meets the requirements.

[0039] Similarly, in the method for preparing the 2-13 μm mid-to-far infrared antireflection film on a germanium substrate according to the present disclosure, by using YF 3 With Y 2 O 3 The outermost protective layer is formed by reinforcing and combining Ge, ZnS, and YF 3 , Y 2 O 3 When the transmittance of the four film materials and the germanium substrate meets the requirements in the mid-to-far infrared band of 2-13μm, the outermost protective layer in the designed film structure plays a role in improving hardness, enhancing resistance to mechanical friction and moisture and corrosion resistance, especially improving moisture and corrosion resistance.

[0040] The cleaning in step S1 is beneficial to improving the surface conditions of the first and second surfaces of the lens, and is helpful to improving the bonding performance between the film structure on each surface and the corresponding surface of the lens. For example, ultrasonic or hand wiping is used to clean the surface of the lens. For example, the thickness of the accompanying plating sheet is 1.0 mm.

[0041] In one example, in step S2, the thickness of the film layer in the film system process parameters is based on the aforementioned optimal film thickness stored in the control computer of the coating machine, that is, for each of the two sides of the germanium substrate, the optimal film thickness of the film layer is: the film thickness of the first ZnS film layer is 26.25±3nm, the film thickness of the second Ge film layer is 103.16±3nm, the film thickness of the third ZnS film layer is 71.92±3nm, the film thickness of the fourth Ge film layer is 102.24±3nm, the film thickness of the fifth ZnS film layer is 120.86±3nm, the film thickness of the sixth Ge film layer is 70.99±3nm, the film thickness of the seventh ZnS film layer is 185.15±3nm, the film thickness of the eighth Ge film layer is 33.83±3nm, the film thickness of the ninth ZnS film layer is 337.30±3nm, and the film thickness of the tenth YF film layer is 100. 3 The film thickness of the film layer is 29.96±3nm, the film thickness of the eleventh ZnS film layer is 157.82±3nm, and the film thickness of the twelfth YF 3 The thickness of the film layer is 204.99±3nm, the thickness of the thirteenth ZnS film layer is 95.64±3nm, and the thickness of the fourteenth YF 3 The thickness of the film layer is 602.18±3nm, and the fifteenth layer Y 2 O 3 The film thickness is 20±5nm; the evaporation mode of the film material is Ge and Y 2 O 3 Using electron beam heating evaporation, ZnS and YF 3 The deposition rate of the film material is: The deposition rate of the Ge film layer is Y 2 O 3 The deposition rate of the film is The deposition rate of the ZnS film is YF 3 The deposition rate of the film is The use of ion source assisted deposition is: coating the first layer of ZnS film, coating the tenth layer of YF 3 Film layer, 12th layer YF 3 Film layer, 14th layer YF 3 Film layer, fifteenth layer Y 2 O 3 The film layer is deposited with ion source assistance, and the other layers are not deposited with ion source assistance. Using ion source assistance deposition can make the corresponding film layer denser and more uniform.

[0042] Further, in one example, the ion source parameters for coating the first ZnS film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon gas flow rate in the neutralization gas is 100%; the ion source parameters for coating the tenth YF 3Film layer, 12th layer YF 3 Film layer, 14th layer YF 3 The ion source parameters for the film layer are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 100V, anode current 1A, and argon gas flow in the neutralization gas is 100%; the fifteenth layer of Y 2 O 3 The ion source parameters during membrane formation were: neutralization current 0.5 A, neutralization gas flow rate 8 sccm, anode voltage 180 V, anode current 1.8 A, argon flow rate in neutralization gas 20%, and oxygen flow rate in neutralization gas 80%.

[0043] The baking in step S3 is to prepare the temperature for the pre-melting of the film material. The pre-melting of the film material can release the gas in the film material and remove the impurities in the film material to ensure the purity of the film material, thereby reducing the adverse factors that affect the quality of the film layer during the film coating process in step S5 described later. In addition, baking also heats the lens. Specifically, in one example, in step S3, the temperature of the chamber of the coating machine is set to 150°C; when the vacuum reaches (4.0-6.0)×10 -3 The film material is pre-melted at 150°C and maintained at this constant temperature for 10 minutes.

[0044] The ion source cleaning in step S4 uses ion bombardment to clean the surface microstructure of the lens, which can eliminate the oxide layer on the surface of the lens, making the surface of the lens cleaner and conducive to the firm adhesion and growth of the film layer. Specifically, in one example, in step S4, when the vacuum degree reaches (0.9-1.0)×10 -3 Pa, start the ion source of the vacuum coating machine, set the ion cleaning parameters of the ion source as follows: neutralization current 0.8-1.0A, neutralization gas flow 8-10sccm, anode voltage 200-220V, anode current 2-2.5A, argon flow in neutralization gas 100%, and cleaning time 5-8min.

[0045] In one example, in step S5, argon gas is introduced and vacuum is drawn to maintain a constant vacuum when each film layer is deposited, and the constant vacuum is set to be no less than 5.0×10 -3 Pa; the first to fourteenth film layers are evaporated at a chamber temperature of 150°C in the coating machine, and the fifteenth layer Y 2 O 3The film layer is evaporated at a temperature of 180°C when the chamber temperature of the coating machine is raised. The first to fourteenth film layers are evaporated at 150°C and the fifteenth film layer is evaporated at 180°C, which is beneficial to the growth of the corresponding film layer. In one example, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5.7MHz.

[0046] In one example, in step S6, after plating is completed, the chamber is kept at a constant temperature of 180°C for 5 minutes to release the internal stress of the film structure.

[0047] In one example, in step S7, the door is opened to take out the items after the temperature drops below 90°C.

[0048] [test]

[0049] Example 1

[0050] Part 1: Design method of 2-13μm mid- and far-infrared antireflection films on germanium substrates

[0051] The design method of the germanium substrate 2-13 μm mid- and far-infrared antireflection film of Example 1 adopts the following steps:

[0052] Sa, 6.5μm is selected as the reference wavelength for the design of 1 / 4 wavelength film thickness of optical thin films, using the film stack formula:

[0053] Sub / 0.04L / 0.3H / 0.1L / 0.3H / 0.2L / 0.2H / 0.3L / 0.1H / 0.5L / 0.03M / 0.2L / 0.2M / 0.15L / 0.6M / 0.02Q / AIR,

[0054] Among them, Sub is the germanium substrate, AIR represents air, H represents the high refractive index material Ge (germanium) with a film thickness of 1 / 4 wavelength, L represents the low refractive index material ZnS (zinc sulfide) with a film thickness of 1 / 4 wavelength, and M represents the intermediate refractive index material YF with a film thickness of 1 / 4 wavelength. 3 (yttrium fluoride), Q represents the outermost layer material Y of the film layer with a thickness of 1 / 4 wavelength 2 O 3 (yttrium oxide);

[0055] Sb, the film thickness is calculated and optimized by design software to obtain the best film thickness. The transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13μm meets the requirements;

[0056] Sc, input the optimized film thickness into the control computer of the coating machine;

[0057] Wherein, in step Sb, for each of the two sides of the germanium substrate, the optimal film thickness of the film layer is:

[0058] The thickness of the first ZnS film layer is 26.25nm.

[0059] The thickness of the second Ge film layer is 103.16nm.

[0060] The thickness of the third ZnS film is 71.92nm.

[0061] The thickness of the fourth Ge film layer is 102.24nm.

[0062] The thickness of the fifth ZnS film layer is 120.86nm.

[0063] The thickness of the sixth Ge film layer is 70.99nm.

[0064] The thickness of the seventh ZnS film layer is 185.15nm.

[0065] The thickness of the eighth Ge film layer is 33.83nm.

[0066] The thickness of the ninth ZnS film layer is 337.30nm.

[0067] Tenth floor YF 3 The film thickness is 29.96nm.

[0068] The thickness of the eleventh ZnS film layer is 157.82nm.

[0069] 12th floor YF 3 The film thickness is 204.99nm.

[0070] The thickness of the thirteenth ZnS film layer is 95.64nm.

[0071] 14th floor YF 3 The film thickness is 602.18nm.

[0072] Fifteenth Floor Y 2 O 3 The film thickness of the film layer is 20nm;

[0073] In step Sb, the design software is TFCalc.

[0074] Figure 2 1 is a transmittance curve diagram of the film stack design optimization diagram of the design method of the germanium substrate 2-13 μm mid-to-far infrared anti-reflection film according to the present disclosure in Example 1. Figure 2 It can be seen that the transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13 μm is greater than 95% on average.

[0075] Part II: Preparation method of 2-13μm mid- and far-infrared antireflection film on germanium substrate

[0076] The method for preparing the 2-13 μm mid-to-far infrared antireflection film on a germanium substrate of Example 1 comprises the following steps:

[0077] S1, before plating, ultrasonic cleaning is used for the accompanying plated sheets and products of the germanium substrate used as lenses, and Ge, ZnS, YF 3 , Y 2 O 3 Four types of film material preparation work, among which the thickness of the accompanying plating sheet is 1.0mm;

[0078] S2, vacuum coating machine is a vacuum coating machine with a Hall ion source equipped with a neutralizer manufactured and sold by Chengdu Siwork Vacuum Technology Co., Ltd., the Hall ion source equipped with a neutralizer is purchased from Boton Optoelectronics Technology Co., Ltd., the film system process parameter configuration, the film system process parameter configuration includes the optimal film thickness, film material evaporation mode, film material deposition rate, and the use of ion source assisted deposition. The film thickness in the film system process parameters is based on the optimal film thickness stored in the control computer of the coating machine in the first part above, and the film material evaporation mode is Ge and Y 2 O 3 Using electron beam heating evaporation, ZnS and YF 3 Using resistance heating evaporation, the deposition rate of the film material is: the deposition rate of the Ge film layer is Y 2 O 3 The deposition rate of the film is The deposition rate of the ZnS film is YF 3 The deposition rate of the film is The use of ion source assisted deposition is: coating the first layer of ZnS film, coating the tenth layer of YF 3 Film layer, 12th layer YF 3 Film layer, 14th layer YF 3 Film layer, fifteenth layer Y 2 O 3 The ion source assisted deposition was used for the first ZnS film layer, and the other layers were not deposited with ion source assisted deposition. The ion source parameters for the first ZnS film layer were: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 120V, anode current 1.2A, and argon gas flow in neutralization gas 100%; the tenth YF 3 Film layer, 12th layer YF 3 Film layer, 14th layer YF 3 The ion source parameters for the film layer are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 100V, anode current 1A, and argon gas flow in the neutralization gas is 100%; the fifteenth layer of Y2 O 3 The ion source parameters during membrane formation were: neutralization current 0.5 A, neutralization gas flow rate 8 sccm, anode voltage 180 V, anode current 1.8 A, argon flow rate in neutralization gas 20%, oxygen flow rate in neutralization gas 80%;

[0079] S3, put the cleaned lens into the fixture, hang the fixture into the cavity of the coating machine, vacuum bake, pre-melt the film material, degas, remove impurities and keep the temperature constant. The temperature of the cavity of the coating machine is set to 150℃. When the vacuum reaches 4.0×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 10 minutes.

[0080] S4, ion source cleaning lens, when the vacuum reaches 1.0×10 -3 Pa, start the ion source of the vacuum coating machine, and set the ion cleaning parameters of the ion source as follows: neutralization current 1.0A, neutralization gas flow rate 10sccm, anode voltage 220V, anode current 2A, argon gas flow rate in neutralization gas 100%, and cleaning time 8min;

[0081] S5, film coating and monitoring, according to the film system parameter process configuration of step S2, the film layer is coated on the first surface of the lens, and argon gas is introduced and vacuumed to maintain the flow type constant vacuum when coating each film layer. The constant vacuum degree is set to 5.0×10 -3 Pa, the first to fourteenth film layers are evaporated at a chamber temperature of 150°C in the coating machine, and the fifteenth layer Y 2 O 3 The film layer is evaporated when the chamber temperature of the coating machine is raised to 180°C. The film thickness is monitored by using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller using the crystal oscillator method. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator of the multiple crystal oscillators. The crystal oscillator frequency is 6MHz.

[0082] S6, after plating is completed, the cavity is kept at a constant temperature of 180°C for 5 minutes;

[0083] S7, wait until the temperature drops below 90°C, open the door and take out the items;

[0084] S8, repeating steps S1 to S7 to perform film coating on the second surface of the lens.

[0085] Comparative Example 1

[0086] Except for the first and second parts, the outermost Y is omitted 2 O 3 layer (i.e. the fifteenth film layer) and the outermost layer Y 2 O3 Except for the plating of the layer, the rest is the same as in Example 1.

[0087] Comparative Example 2

[0088] In addition to the fifteenth layer Y in step S5 of the second part 2 O 3 The film layer is evaporated at a chamber temperature of 150° C. in the coating machine, and the rest is the same as in Example 1.

[0089] Figure 3 The curve diagram of the transmittance in the 2-13 μm band of the accompanying plate of Example 1 coated with 2-13 μm mid- and far-infrared anti-reflection films on both sides. Figure 3 It can be seen that the transmittance of the prepared germanium substrate in the mid-to-far infrared band of 2-13 μm is greater than 95% on average.

[0090] In accordance with GJB2485A-2019, the following tests were performed on Example 1, Comparative Example 1 and Comparative Example 2 after coating on both sides.

[0091] Water bubble test: Take tap water to conduct a water bubble test for 2 hours to observe whether the film layer on each surface falls off from the accompanying plating sheet and whether the film layer on each surface is cracked.

[0092] Salt spray test: neutral salt spray test for 48 hours, observe whether the film layer on each side of the accompanying plating sheet falls off, observe whether the film layer on each side of the accompanying plating sheet cracks.

[0093] Adhesion test: Use hand to stick 3M tape on each side of the plating sheet and pull the tape in the direction opposite to the sticking end to observe whether the film layer is pulled up.

[0094] Thermal shock test: In a high and low temperature box, perform thermal shock test in the range of -40℃ to 85℃ for 24 hours to observe whether the film layers on each side of the accompanying plating sheet fall off or crack.

[0095] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, observe whether the film layers on each side of the accompanying plating sheet fall off or crack.

[0096] Friction resistance test (moderate friction test): Wrap the rubber friction head of the friction machine with degreased cloth, apply a pressure of 4.9N on the film surface of the accompanying plating sheet and rub it 50 times (25 times back and forth), and observe whether there are signs of scratches or damage on the surface of the film layer.

[0097] Low temperature test: In a low temperature box, at -40℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off, and observe whether the film layers on each side of the accompanying plating sheet crack.

[0098] High temperature test: In a high temperature box, at 85℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off, and observe whether the film layers on each side of the accompanying plating sheet crack.

[0099] Table 1 shows the transmittance of Example 1 and Comparative Examples 1-2 and the results of various tests.

[0100] Table 1 Transmittance of Example 1 and Comparative Examples 1-2 and results of various tests

[0101]

[0102] From Comparative Example 1 and Example 1, it can be seen that in Comparative Example 1, the outermost layer of the film structure is YF 3 Although the film structure of Comparative Example 1 has good firmness and friction resistance in the environmental adaptability test, it failed the salt spray test and constant temperature and humidity test. The film is prone to moisture absorption and corrosion in a hot and humid salt spray environment for a long time, which leads to a decrease in the durability of the film. Therefore, it is necessary to consider strengthening the YF 3 The moisture and corrosion resistance of the film layer is improved, and Example 1 increases Y 2 O 3 As the outermost layer of the membrane structure, the membrane layer can improve the moisture-proof and corrosion-resistant capabilities.

[0103] Further, it can be seen from Comparative Example 2 and Example 1 that Y 2 O 3 The temperature of the film during coating is lower than that of Example 1, and the salt spray test fails. The temperature increase of Example 1 (under ion source assisted deposition) can effectively optimize Y 2 O 3 The growth conditions of the film make Y 2 O 3 The film layer is denser, thus achieving the effect of moisture-proof and corrosion-resistant.

[0104] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A design method for a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate, characterized in that: Includes steps: Sa, 6.5μm is selected as the reference wavelength for the design of 1 / 4 wavelength film thickness of optical thin films, using the film stack formula: Sub / 0.04L / 0.3H / 0.1L / 0.3H / 0.2L / 0.2H / 0.3L / 0.1H / 0.5L / 0.03M / 0.2L / 0.2M / 0.15L / 0.6M / 0.02Q / AIR, Wherein, Sub is the germanium substrate, AIR represents air, H represents the high refractive index material Ge (germanium) with a film thickness of 1 / 4 wavelength, L represents the low refractive index material ZnS (zinc sulfide) with a film thickness of 1 / 4 wavelength, M represents the intermediate refractive index material YF3 (yttrium fluoride) with a film thickness of 1 / 4 wavelength, and Q represents the outermost layer material Y2O3 (yttrium oxide) with a film thickness of 1 / 4 wavelength; Sb, the film thickness is calculated and optimized by design software to obtain the best film thickness. The transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13μm meets the requirements; Sc, the optimized film thickness is input into the control computer of the coating machine.

2. The design method of the 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 1, characterized in that: In step Sb, for each of the two sides of the germanium substrate, the optimal film thickness of the film layer is: The thickness of the first ZnS film is 26.25±3nm. The thickness of the second Ge film layer is 103.16±3nm. The thickness of the third ZnS film is 71.92±3nm. The thickness of the fourth Ge film layer is 102.24±3nm. The thickness of the fifth ZnS film is 120.86±3nm. The thickness of the sixth Ge film layer is 70.99±3nm. The thickness of the seventh ZnS film is 185.15±3nm. The thickness of the eighth Ge film layer is 33.83±3nm. The thickness of the ninth ZnS film layer is 337.30±3nm. The thickness of the tenth YF3 film is 29.96±3nm. The thickness of the eleventh ZnS film layer is 157.82±3nm. The thickness of the twelfth YF3 film is 204.99±3nm. The thickness of the thirteenth ZnS film layer is 95.64±3nm. The thickness of the fourteenth YF3 film layer is 602.18±3nm. The thickness of the fifteenth Y2O3 film layer is 20±5nm; In step Sb, the transmittance of the optimized germanium substrate in the mid-to-far infrared band of 2-13 μm is greater than 95% on average.

3. The design method of the 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 1, characterized in that: In step Sb, the design software is TFCalc, Essential Macleod, OptiLayer, Filmstar, Filmmaster, and Autofilm.

4. A method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate, characterized in that: Includes steps: S1, before plating, clean the accompanying plating sheet and products as the germanium substrate of the lens and prepare the four film materials of Ge, ZnS, YF3 and Y2O3; S2, film system process parameter configuration, the film system process parameter configuration includes the optimal film thickness of the film layer, the evaporation mode of the film material, the deposition rate of the film material, and the use of ion source assisted deposition, and the film thickness of the film system process parameters is based on the optimal film thickness of the film layer stored in the control computer of the coating machine according to any one of claims 1-3; S3, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake, pre-melt the film material, release air, remove impurities and keep the temperature constant; S4, ion source cleaning lens; S5, coating and monitoring the film layer, coating the film layer on the first surface of the lens according to the film system parameter process configuration of step S2; S6, constant temperature maintenance after plating; S7, cooling and picking up; S8, repeating steps S1 to S7 to perform film coating on the second surface of the lens.

5. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 4, characterized in that: In step S1, Cleaning is done by ultrasonic cleaning and manual wiping; The thickness of the accompanying plating sheet is 1.0 mm.

6. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 4, characterized in that: In step S2, The thickness of the film layer in the film system process parameters is based on the optimal film thickness of the film layer stored in the control computer of the coating machine according to claim 2; The evaporation mode of the film materials is that Ge and Y2O3 use electron beam heating evaporation, and ZnS and YF3 use resistance heating evaporation; The deposition rate of the film material is: The deposition rate of the Ge film layer is The deposition rate of the Y2O3 film is The deposition rate of the ZnS film is The deposition rate of the YF3 film is The use of ion source assisted deposition is: ion source assisted deposition is used when plating the first ZnS film layer, the tenth YF3 film layer, the twelfth YF3 film layer, the fourteenth YF3 film layer, and the fifteenth Y2O3 film layer, and ion source assisted deposition is not used for the remaining layers.

7. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 6, characterized in that: The ion source parameters when depositing the first ZnS film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon gas flow rate in neutralization gas 100%; The ion source parameters when depositing the tenth YF3 film layer, the twelfth YF3 film layer, and the fourteenth YF3 film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon gas flow rate in neutralization gas is 100%; The ion source parameters when depositing the fifteenth layer of Y2O3 film are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 180V, anode current 1.8A, argon flow rate in neutralization gas 20%, and oxygen flow rate in neutralization gas 80%.

8. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 4, characterized in that: In step S3, The temperature of the coating machine chamber is set to 150°C; When the vacuum reaches (4.0-6.0)×10 -3 The film material is pre-melted at 150°C and maintained at this constant temperature for 10 minutes.

9. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 4, characterized in that: In step S4, When the vacuum degree reaches (0.9-1.0)×10 -3 Pa, start the ion source of the vacuum coating machine, The ion cleaning parameters of the ion source were set as follows: neutralization current 0.8-1.0 A, neutralization gas flow rate 8-10 sccm, anode voltage 200-220 V, anode current 2-2.5 A, argon flow rate in neutralization gas 100%, and cleaning time 5-8 min.

10. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 4, characterized in that: In step S5, When coating each film layer, argon gas is introduced and vacuum is drawn to maintain the flow type constant vacuum, and the constant vacuum is set to no less than 5.0×10 -3 Pa; The first to fourteenth film layers are deposited at a temperature of 150°C in the chamber of the coating machine, and the fifteenth Y2O3 film layer is deposited at a temperature of 180°C in the chamber of the coating machine; The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.7MHz.

11. The method for preparing a 2-13 μm mid- and far-infrared antireflection film on a germanium substrate according to claim 4, characterized in that: In step S6, after the plating is completed, the cavity is kept at a constant temperature of 180°C for 5 minutes; In step S7, the door is opened to take out the items when the temperature drops below 90°C.

Citation Information

Patent Citations

  • Preparation method for large-angle multiband infrared high antireflection film system

    CN105607159A

  • Germanium substrate 8-12 [mu] m infrared band diaphragm and preparation method thereof

    CN114200552A

  • Cone mirror in long-wave infrared optical system

    CN114924339A

  • Medium-long wave infrared composite anti-reflection protective film and preparation method thereof

    CN118441244A

  • Antireflection film for infrared light

    JP2007298661A